Extrinsic anomalous Hall effect in van der Waals ferromagnet Fe5GeTe2 - Ryuki Suzuki; Tenghua Gao; Hiroki Nakayama; Kazuya Ando (AIP Advances, 2023)
We investigate the anomalous Hall effect in a van der Waals material Fe5GeTe2. We find a distinct difference in the temperature dependence of the anomalous Hall effect associated with the evolution of magnetic states in Fe5GeTe2 films. In the low-temperature region, the anomalous Hall conductivity changes with the longitudinal conductivity, which highlights the substantial contribution from the extrinsic mechanism. The extracted skew scattering coefficient in the Fe5GeTe2 films is an order of magnitude larger than that in transition metal ferromagnets. This result sheds light on the role of the extrinsic mechanism in the anomalous Hall effect in van der Waals magnets.